Physiological and Molecular Investigation of Urea Uptake Dynamics in Cucumis sativus L. Plants Fertilized With Urea-Doped Amorphous Calcium Phosphate Nanoparticles - Feil, Sebastian B.; Rodegher, Giacomo; Gaiotti, Federica; Alzate Zuluaga, Monica Yorlady; Carmona, Francisco J.; Masciocchi, Norberto; Cesco, Stefano; Pii, Youry (Frontiers in Plant Science, 2021)
At present, the quest for innovative and sustainable fertilization approaches aiming at improving agricultural productivity represent one of the major challenges for the research. In this context, nanoparticles-based fertilizers can indeed offer an interesting alternative with respect to traditional bulk fertilizers. Several pieces of evidence have already addressed the effectiveness of amorphous calcium phosphate -based nanoparticles as carriers for macronutrients as nitrogen (N), demonstrating increase in crops productivity and improvement in quality. Nevertheless, despite being N a fundamental nutrient for crop growth and productivity, very little research has been carried out to understand the physiological and molecular mechanisms underpinning N-based fertilizers supplied to plants via nanocarriers. For these reasons, the present study aimed at investigating the responses of Cucumis sativus L. to amorphous calcium phosphate nanoparticles doped with urea (U-ACP). Urea uptake dynamics at root level have been investigated by monitoring both the urea acquisition rates and the modulation of urea transporter CsDUR3, whereas growth parameters, the accumulation of N in both root and shoots, and the general ionomic profile of both tissues have been determined to assess the potentiality of U-ACP as innovative fertilizers. The slow release of urea from nanoparticles and/or their chemical composition contributed up-regulating the urea uptake system for a longer period (up to 24 hours after treatment) as compared to plants treated with bulk urea. This prolonged activation was mirrored by a higher accumulation of N in nanoparticles-treated plants (approximately 3-fold increase in shoot of NP treated plants compared to controls), even when the concentration of urea conveyed through nanoparticles was halved. In addition, besides impacting N nutrition, U-ACP also enhanced Ca and P concentration in cucumber tissues, thus having possible effects on plants growth and yield, and on the nutritional value of the agricultural products.